UMUMIY O‘RTA TA’LIM MAKTABLARIDA LABORATORIYA MASHG‘ULOTLARINI O‘TKAZISH METODIKASI (10-sinf misolida) - Kamolova, U.A.; Amirullayeva, B.A. (SCIENCE and SOCIETY, 2022)
Current article discusses the laboratory work in public education schools, the technical safety rules, measurement errors, and the use of modern equipment and tools in the 10th grade training program, developed on the basis of a competing approach.